2022
DOI: 10.3390/ijms23126410
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Agronomical, and Proteomic Studies Reveal Crucial Players in Rice Nitrogen Use Efficiency under Low Nitrogen Supply

Abstract: Excessive use of nitrogenous fertilizers to enhance rice productivity has become a significant source of nitrogen (N) pollution and reduced sustainable agriculture. However, little information about the physiology of different growth stages, agronomic traits, and associated genetic bases of N use efficiency (NUE) are available at low-N supply. Two rice (Oryza sativa L.) cultivars were grown with optimum N (120 kg ha−1) and low N (60 kg ha−1) supply. Six growth stages were analyzed to measure the growth and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…In the present study, 10 N-efficient and 10 N-inefficient genotypes screened at the seedling stage were assessed for N adaptation in the field under normal N (N90) and low-N (N0) conditions. N-efficient genotypes with high productivity can effectively relieve environmental stress and achieve nitrogen reduction, which has practical implications [28], so more desirable N-efficient genotypes are supposed to be both highly N-efficient and highly productive [21]. Peanut yield differed significantly among the genotypes [29], which was indirectly influenced by the number of pods and full pods per plant, 100 pod weight, and 100 kernel weight.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 10 N-efficient and 10 N-inefficient genotypes screened at the seedling stage were assessed for N adaptation in the field under normal N (N90) and low-N (N0) conditions. N-efficient genotypes with high productivity can effectively relieve environmental stress and achieve nitrogen reduction, which has practical implications [28], so more desirable N-efficient genotypes are supposed to be both highly N-efficient and highly productive [21]. Peanut yield differed significantly among the genotypes [29], which was indirectly influenced by the number of pods and full pods per plant, 100 pod weight, and 100 kernel weight.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nitrogen inhibitors, the split application of nitrogen, irrigation time, and the correct placement method of fertilizer which takes into consideration soil and crop type could improve NUE [ 93 , 94 , 95 , 96 ]. Therefore, melatonin must be studied more widely in the agronomic field in order to be considered a possible input into the NUE strategy [ 12 , 16 , 97 ], including the effects of enhancement by melatonin in the assimilation and metabolization of nitrogen, especially in symbiotic plants [ 54 , 55 ]. It is also important to study the effect of melatonin on rhizosphere and its microbiome, on which there are already some promising data [ 87 , 88 , 89 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, overuse of nitrogen can result in decreased crop productivity. Therefore, producing more whilst using less nitrogen, the so-called Nitrogen Use Efficiency (NUE), is a recommended practice [ 10 , 11 , 12 ]. Currently, the use of “smart fertilizers”, such as coated fertilizers, and the application of plant-growth-promoting rhizobacteria (PGPR) to the soil has ostensibly improved the nutrition of nitrogen in plants [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these genes have been proven to be of general importance for photosynthesis and plant growth, including PSII dissolved oxygen enhancing proteins, cytochrome b6/f complex proteins, PSI subunits, FNRs, and Rubisco (Ermakova et al, 2019;Meng et al, 2021), which is consistent with our hypothesis that the identified DEGs in sugar beet played key roles in nitrogen use efficiency (NUE) under low nitrogen conditions. Many studies have reported that low nitrogen stress affects photosynthesis by affecting light and dark reactions in chloroplasts (Sultana et al, 2020;Tantray et al, 2022). Excited energy captured by the LHC is transferred to the core antenna complex and ultimately used in PSI and PSII reaction centers (RCs) for photochemical reactions.…”
Section: The Crucial Role Of Downregulated Degs In the Photosynthesis...mentioning
confidence: 99%
“…Under stress conditions, different levels of regulation exist in cells to maintain a properly balanced metabolic ratio between carbon and nitrogen, which is necessary to avoid metabolic inefficiencies (Zhang et al, 2018a). In plants, photosynthesis is the energy source for carbon and nitrogen metabolism, and nitrogen deficiency has been reported to significantly reduce the photosynthetic capacity of plants (Tantray et al, 2022). Low nitrogen significantly attenuated the expression of genes controlling nitrogen metabolism (Figure 8, Supplementary Table 6).…”
Section: The Crucial Role Of Downregulated Degs In the Photosynthesis...mentioning
confidence: 99%